Impact of resistance exercise on experimental pain perception and perceived exertion, in the trained athletes exercising in a hot climate - Lotfi, S.; Jaziz, A.; Zerdani, I.; Tazi, A. (World Journal of Sport Sciences, 2015)
The aim of this research is investigating the effect of resistance exercise on the level of perceived pain caused by the experimental thermal heat. 11 athletes took part voluntarily in this research, aged 23.02 ±0.7 years, were assessed at rest (baseline levels) and after resistance exercise (accomplished in a hot climate 30.7°C)on duration of the hand immersed in hot water, physical fatigue, pain perception level, using the Verbal Analogue Scale (VAS) and Borg's RPE scale. Comparing to baseline levels, the values immersion time (36.05 ±5.15vs 12.78 ±3.87) increase, and pain perception level (5.43 ±1.90 vs 8.86 ±1.46) decreased significantly (p<0, 0.028, p<0.041) after the exercise. We also identified, a significantly negative high correlation (r = 0.846, p>0.008,) between the run performance (In time) and Borg RPE value and a significant correlation (r = 0.516, p<0.044) between pain perception level and the difficulty of perceived exertion. The resistance exercise performed in warm climate increases the sensitivity of pain physically perceived and felt. The body uses its own strategies to extend the suffering induced by resistance exercise to hot external stimuli